132 The utilisation of non-cardiac services by a heart attack centre. (22nd September 2015) - Sharma, A; Ramli, R; Mohiddin, S; Knight, C; Rothman, M; Mathur, A; Wragg, A
Abstract : Introduction: Most patients with ST-elevation myocardial infarction (STEMIs) within the London area are transferred to Heart Attack Centres (HAC) for primary percutaneous coronary intervention. HACs may be stand-alone centres, combined with cardiac surgery and cardiac ITU or part of a large single site acute hospitals. It is not clear whether these different models impact on patient pathways and care. We investigated the utilisation of non-cardiology services (including cardiac surgery and ITU) of patients admitted to a single London HAC. Methods: We undertook a retrospective data analysis of 300 consecutive patients presenting with ST-elevation myocardial infarction to the London Chest Hospital, Barts and The London NHS Trust between January and June 2009. The cardiology databases and hospital care record systems were examined to identify all episodes and encounters generated by non-cardiology clinical activity. We also assessed use of cardiac surgery and intensive care during the index admission. Results: Twelve (4%) of patients with STEMIs presenting to a HAC required clinical services outside the HAC infrastructure. 6 (2%) required either telephone advice or visit from a non-cardiac specialist and 6 (2%) required in-patient transfer to another clinical service. Inpatient transfer was due to complications of coronary intervention 3 (1%) or for management of newly diagnosed/ chronic non-cardiac conditions 3 (1%). No adverse outcomes were recorded due to delays in accessing non-cardiac care. ITU admission was required in 13 (4%) of HAC patients. The mean length of ITU stay was 11 days and the HAC service required an average of 0.8 ITU beds/day. Eighteen (5%) of HAC patients required inpatient CABG, 8/18 as emergency procedures. Conclusion: Almost all STEMI patients can be managed within a HAC, and the utilisation of non-cardiac services is minimal suggesting that HACs can be located separately from acute general hospitals. However the importance of ITU and cardiac surgical services suggests that patient pathways are safer and more efficient if these services are on-site with the HAC. The greater risks of adverse outcomes following emergency surgery is another implication for surgical centres attached to the HAC.